High‐Pressure Mechanical Properties of Talc: Implications for Fault Strength and Slip Processes. Issue 3 (23rd February 2023) - Boneh, Y.; Pec, M.; Hirth, G.
Abstract: The hydrous mineral talc is stable over a relatively large P‐T field and can form due to fluid migration and metamorphic reactions in mafic and ultramafic rocks and in faults along plate boundary interfaces. Talc is known to be one of the weakest minerals, making it potentially important for the deformation dynamics and seismic characteristics of faults. However, little is known about talc's mechanical properties at high temperatures under confining pressures greater than 0.5 GPa. We present results of deformation experiments on natural talc cylinders exploring talc rheology under 0.5–1.5 GPa and 400–700°C, P‐T conditions simulating conditions at deep faults and subducted slab interface. At these pressures, the strength of talc is highly temperature‐dependent where the thermal weakening is associated with an increased tendency for localization. The strength of talc and friction coefficient inferred from Mohr circle analysis is between 0.13 at 400°C to ∼0.01 at 700°C. Strength comparison with other phyllosilicates highlights talc as the weakest mineral, a factor of ∼3–4 weaker than antigorite and a factor of ∼2 weaker than chlorite. The observed friction coefficients for talc are consistent with those inferred for subducted slabs and the San Andreas fault. We conclude that the presence of talc may explain the low strength of faults and of subducted slab interface at depths where transient slow slip events occur. Plain Language Summary: Whether faults creep by slow continuous and stable motion, generate slow slip or low‐frequency seismicity, or rupture by an unstable spontaneous event (i.e., an earthquake) is related to the mechanical properties of the minerals in place. Talc is one of the weakest minerals and is expected to form in fault interfaces. There is a lack of experimental data on the mechanical properties of talc under the pressures and temperatures that exist along deep faults and subduction zones. Here, we present results from a set of deformation experiments on talc under pressure‐temperature conditions that simulate deep faults and subducted slab interface. Results show a transition from pressure‐dependent to pressure‐independent strength at high temperatures (∼700°C). In addition, at increased temperature (≥600°C) talc shows an increased tendency for strain localization. These extremely low frictional strengths are about an order of magnitude lower than most rocks and are consistent with inferred weak interfaces along the San Andreas fault and various subducted slab interfaces at depths where creep and/or slow slip events occur. Key Points: Talc strength is pressure‐ and temperature‐dependent under conditions of deep faults and subduction zones (0.5–1.5 GPa and 400–700°C) Talc microstructure shows fracturing under all conditions tested associated with thermal weakening and increased localization The extremely low friction coefficient (<0.13) is consistent with the inferred strength of different subducted slab interfaces and the San Andreas fault